Changing the research landscape: the New York City Clinical Data Research Network. (12th May 2014) - Kaushal, Rainu; Hripcsak, George; Ascheim, Deborah D; Bloom, Toby; Campion, Thomas R; Caplan, Arthur L; Currie, Brian P; Check, Thomas; Deland, Emme Levin; Gourevitch, Marc N; Hart, Raffaella; Horowitz, Carol R; et al.
Abstract: The New York City Clinical Data Research Network (NYC-CDRN), funded by the Patient-Centered Outcomes Research Institute (PCORI), brings together 22 organizations including seven independent health systems to enable patient-centered clinical research, support a national network, and facilitate learning healthcare systems. The NYC-CDRN includes a robust, collaborative governance and organizational infrastructure, which takes advantage of its participants' experience, expertise, and history of collaboration. The technical design will employ an information model to document and manage the collection and transformation of clinical data, local institutional staging areas to transform and validate data, a centralized data processing facility to aggregate and share data, and use of common standards and tools. We strive to ensure that our project is patient-centered; nurtures collaboration among all stakeholders; develops scalable solutions facilitating growth and connections; chooses simple, elegant solutions wherever possible; and explores ways to streamline the administrative and regulatory approval process across sites.